Training of HOTS integration in elementary school level mathematics teaching as an effort to strengthen state defense awareness - Stiawan, Elva; Basuki, Rahmat; Prawira, Ajeng Arimby Setyaningsih Putri Yan (Journal of Community Service and Empowerment, 2024)
Strengthening state defense awareness could be supported by the existence of educators from remote and border areas who have adequate performance of high-order thinking skills (HOTS). Currently, HOTS has not been consistently introduced in mathematics learning for teachers in remote areas. This study is a part of the teachers’ development program concerned with delivering effective methods in teaching mathematics at the elementary school level and gaining teachers’ State Defense Awareness to provide educators’ perspectives regarding HOTS implementation in mathematics learning in remote areas of Indonesia. Data was collected by giving questionnaires to the teachers as pre-tests and post-tests. The results showed that the teachers of some remote areas recognized the advantages as well as the difficulties of HOTS integration in learning activities. Teachers' understanding of applying HOTS in mathematics teaching could be slightly increased through comprehensive training regarding HOTS. It was also found that teachers from remote and border areas are still required to be more encouraged to implement and develop HOTS in mathematics learning through training in education research activities.